Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T16:28:56+01:00
A) y= -3x+7 dla x= -4
y= (-3) × (-4) + 7
y=12+7=19

b) y= -5(x-2)+3 dla x= 1
y=-5(1-2)+3
y=-5+10+3
y=8

c) y= 2 dla x= 0
y=2

d) y= -3 dla x= 1
y=-3

e) s= 3t dla t= 2
s=3×2
s=6

f) s= 6v + 1 dla v= 12
s=6×12+1
s=73
1 5 1
2010-01-07T17:50:49+01:00
W tym zadaniu za x musisz podstawić znaną wartość i obliczyć y. Więc zaczynajmy :)
a) y= -3x+7 dla x= -4
y=-3*(-4)+7=19
b) y= -5(x-2)+3 dla x= 1
y=-5(1-2)+3=8
c) y= 2 dla x= 0
y=2
d) y= -3 dla x= 1
y=-3
e) s= 3t dla t= 2
s=6
f) s= 6v + 1 dla v= 12
s=6*(12)+1=73
Powodzenia :)
1 5 1